Alcohol and tobacco consumption alter hypothalamic pituitary adrenal axis DNA methylation. (April 2016) - Dogan, Meeshanthini V.; Lei, Man-Kit; Beach, Steven R.H.; Brody, Gene H.; Philibert, Robert A.
Highlights: Objective DNA methylation biomarkers can quantify smoking and alcohol consumption. Substance use affects HPA axis DNA methylation. Influence of substance use is more prominent at FKBP5 than NR3C1. Abstract: Alcohol and cigarette consumption have profound effects on genome wide DNA methylation and are common, often cryptic, comorbid features of many psychiatric disorders. This cryptic consumption is a possible impediment to understanding the biology of certain psychiatric disorders because if the effects of substance use are not taken into account, their presence may confound efforts to identify effects of other behavioral disorders. Since the hypothalamic pituitary adrenal (HPA) axis is known to be dysregulated in these disorders, we examined the potential for confounding effects of alcohol and cigarette consumption by examining their effects on peripheral DNA methylation at two key HPA axis genes, NR3C1 and FKBP5. We found that the influence of alcohol and smoke exposure is more prominent at the FKBP5 gene than the NR3C1 gene. Furthermore, in both genes, loci that were consistently significantly associated with smoking and alcohol consumption demethylated with increasing exposure. We conclude that epigenetic studies of complex disorders involving the HPA axis need to carefully control for the effects of substance use in order to minimize the possibility of type I and type II errors.